The pressure distribution of hollow cathode centered negative pressure arc. (August 2016) - Chen, Shujun; Yan, Zhaoyang; Jiang, Fan; Lu, Zhenyang
Abstract: As a newly modified welding heat source, hollow cathode centered negative pressure arc (HCCNPA) has obvious changes in arc morphology and pressure distribution in comparison with traditional gas tungsten arc (GTA). To better understand of these, in this paper the arc behavior was monitored by using a high-speed image processing system. And the influence of the negative pressure in hollow cathode was evaluated to study arc pressure distribution of HCCNPA, the results were compared with the conventional GTAW process. It was found that the application of negative pressure greatly constrains the arc morphology, which comes from the interaction between the negative pressure at the arc root and the ambient atmospheric pressure nearby the arc. The maximum pressure of the HCCNPA was smaller than that of conventional GTA. The application of negative pressure decreases the effect of other parameters such as current and arc length on arc pressure distribution. Though the results showed that the HCCNPA had much lower arc pressure than the conventional GTA, analyses on the bead appearance and cross section provided that the density of HCCNPA energy was more evenly.